Implementasi Proses Rekrutmen dan Seleksi Karyawan pada PT. Bestindo Persada - Dini, Yuli Indah Fajar; Shirlyn, Shirlyn (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
Human resources play a vital role and serve as the key factor in any organization or company. Regardless of the organization's or company's objectives, their implementation and management ultimately depend on human effort. If employee performance does not align with the company's goals, it can result in a decline in overall organizational performance. To address this issue, an analysis of the recruitment and selection system employed by the company is necessary. The methods used to gather data include interviews and observations. The outcome of this practical work is the development of material on effective recruitment and selection processes, followed by an analysis of the recruitment and selection procedures currently implemented by the company.